Collecting Mexico : museums, monuments, and the creation of national identity - Garrigan, Shelley E. (University of Minnesota Press, 2012)
Collecting Mexico centers on the ways in which aesthetics and commercialism intersected in officially sanctioned public collections and displays in late nineteenth-century Mexico. Shelley E. Garrigan reconstructs the lineage of institutionally collected objects around which a modern Mexican identity was negotiated, demonstrating the ways in which displayed objects become linked with nationalistic meaning and why they exert such persuasive force